Flipped classrooms: Making them work for foreign language students - Fielden, Laura V. (2020)
Flipped classrooms are in vogue as an active learning methodology since they combine important pillars of modern education, such as student-centered learning and technology. This model has been applied to different areas and educational levels, though it seems most prominent at the tertiary level. However, it is not clear if it is appropriate for all subject areas, such as language teaching. This paper will explore this question by treating two principal objectives: to review concepts and empirical researchon flipped language classes to ascertain its effectiveness, and secondly, to propose a series of guidelines for language instructors considering flipping their classrooms based on the results from the first objective. Wefind that flipped classrooms may be particularly interesting for communicative language classrooms, and as well as for writing skills improvement.